2014
DOI: 10.1111/ijcp.12377
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of gout in an urban area of Izmir, Turkey: A population-based epidemiological study

Abstract: Our data suggest that the estimated prevalence of gout (0.31%) is lower than the previously published estimated prevalence of rheumatoid arthritis (0.36%) in the same study population (14 definite rheumatoid arthritis cases among the 2835 subjects).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…From our study, the pooled prevalence of gout was 1.1%, which is similar to that in Italy (0.9% in 2009) [ 19 ], France (0.9% in 2013) [ 72 ], the United Kingdom, and Germany (1.4% in 2000–2005) [ 17 ]. In addition, the prevalence of gout in our country was much higher than that in Turkey (0.31% in 2001-2002) [ 73 ], Mexico (0.3% in 2011) [ 74 ], Greece (0.47% in 2003) [ 75 ], and the Czech Republic (0.3% in 2002-2003) [ 76 ] but is markedly lower than that in New Zealand (2.69% in 2008-2009) [ 77 ], the USA (3.9% in 2007-2008) [ 21 ], and Australia (9.7% in 2002) [ 78 ].…”
Section: Discussionmentioning
confidence: 94%
“…From our study, the pooled prevalence of gout was 1.1%, which is similar to that in Italy (0.9% in 2009) [ 19 ], France (0.9% in 2013) [ 72 ], the United Kingdom, and Germany (1.4% in 2000–2005) [ 17 ]. In addition, the prevalence of gout in our country was much higher than that in Turkey (0.31% in 2001-2002) [ 73 ], Mexico (0.3% in 2011) [ 74 ], Greece (0.47% in 2003) [ 75 ], and the Czech Republic (0.3% in 2002-2003) [ 76 ] but is markedly lower than that in New Zealand (2.69% in 2008-2009) [ 77 ], the USA (3.9% in 2007-2008) [ 21 ], and Australia (9.7% in 2002) [ 78 ].…”
Section: Discussionmentioning
confidence: 94%
“… 1 A population-based epidemiological study revealed the estimated prevalence of gout as 0.31% for subjects ≥ 20 years of age, and 0.72% for subjects ≥ 40 years of age in an urban area of Turkey. 2 The burden of gout has increased in the last decades in industrialised countries. This increased incidence is attributed to changes in lifestyle, to related comorbidities including obesity and metabolic syndrome and to prolonged lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…4 In two prevalence studies conducted in Turkey, the prevalence of gout was found to be 0.02% in the Havsa region and 0.31% in the İzmir region. 5,6 Although the frequency of gout varies between societies due to genetic and cultural differences 7 , its prevalence worldwide nearly doubled between 1990 and 2010. 8 This increase may be related to changes in eating habits and increasing obesity rates.…”
Section: Introductionmentioning
confidence: 99%